DETERMINANTS OF ADOLESCENT ATTITUDES TOWARDS ONLINE LOANS IN AN ISLAMIC ECONOMIC PERSPECTIVE - Muthya Elika Fiqroh; Dafiar Syarif; Muhammad Fauzi (Jurnal Dinamika Ekonomi Syariah, 2026)
This study aims to analyze, from the perspective of sharia economics, how sharia financial literacy, self-control, and peer influence on adolescents' attitudes towards online loans in Kerinci Regency. The involvement of teens in legal and illegal online lending has become an important issue, as they are a vulnerable group influenced by their financial knowledge and social environment. This study used a quantitative method with a causal associative design and involved 96 respondents who were selected through purposive sampling. The research instrument was declared valid and reliable. Data were analyzed using multiple linear regression, t-test, F-test, and determination coefficient (R²). The results showed that, in part, Islamic financial literacy and self-control did not have a significant influence on adolescents' attitudes towards online lending, while peer influence had a positive and significant effect. Simultaneously, the three variables had a significant effect, with a value of R² 0.400. These findings emphasize that social factors, especially peer influence, are the main determinants that shape adolescents' attitudes toward online lending